2014
DOI: 10.1007/s10695-014-9934-7
|View full text |Cite
|
Sign up to set email alerts
|

Dietary carotenoids do not improve motility or antioxidant capacity in cichlid fish sperm

Abstract: Carotenoids may act as antioxidants under many circumstances. We examined the importance of carotenoids as antioxidants in the gonads of male convict cichlids (Amatitlania nigrofasciata), a species in which males lack the carotenoid-based breeding coloration that characterizes females. Male fish were fed one of four diets that included different combinations of xanthophyll and carotene carotenoids, and then we measured carotenoid concentration of the gonads, gonadosomatic index (GSI), sperm motility, and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
0
4
2
Order By: Relevance
“…The findings for n3LC‐PUFA confirm recent evidence that PUFAs play an important role in regulating sperm viability in P. reticulata (Rahman et al , ), a finding that has also been reported for other taxa (Al‐Daraji et al , ; Robbins et al , ). The results from this study also corroborate recent evidence that carotenoid intake has no overall main effect on ejaculate traits in P. reticulata or cichlids (Rahman et al , ; Sullivan et al , ), although the evidence for weak interacting effects of carotenoids and n3LC‐PUFA on sperm length provide tentative evidence that any effect of carotenoids on sperm traits may be contingent on other nutrients (Almbro et al , ). Contrary to expectation, however, this study revealed no further evidence that n3LC‐PUFA moderate the action of carotenoids on ejaculate traits (Marri & Richner, ).…”
Section: Composition Of the Experimental Diets Used To Test The Effeccontrasting
confidence: 99%
“…The findings for n3LC‐PUFA confirm recent evidence that PUFAs play an important role in regulating sperm viability in P. reticulata (Rahman et al , ), a finding that has also been reported for other taxa (Al‐Daraji et al , ; Robbins et al , ). The results from this study also corroborate recent evidence that carotenoid intake has no overall main effect on ejaculate traits in P. reticulata or cichlids (Rahman et al , ; Sullivan et al , ), although the evidence for weak interacting effects of carotenoids and n3LC‐PUFA on sperm length provide tentative evidence that any effect of carotenoids on sperm traits may be contingent on other nutrients (Almbro et al , ). Contrary to expectation, however, this study revealed no further evidence that n3LC‐PUFA moderate the action of carotenoids on ejaculate traits (Marri & Richner, ).…”
Section: Composition Of the Experimental Diets Used To Test The Effeccontrasting
confidence: 99%
“…However, this hypothesis seems unlikely since carotenoid supplementation has been shown to increase several components of reproductive investment in various species [29]. Finally, while we acknowledge the possibility that prenatal carotenoid exposure may have detrimental consequences for testes maturation and thus sperm production in our study, we believe that it is inconsistent with the accumulating evidence that carotenoid supplementation improves sperm quality ( [26,28], but see [30]). In addition, the injected carotenoid dose was well within the natural range [17] and yolk carotenoid levels after injection were not unnaturally high since females were fed with a low-carotenoid diet during the whole experiment.…”
Section: Discussioncontrasting
confidence: 55%
“…In mammals, we did not find any studies that measured sperm length. In fish, few studies have quantified testes size (but see Sullivan et al, 2014;Mehlis et al, 2015), we did not find any studies that measured ejaculate/accessory gland size, and most diet manipulations consisted of a reduction in total food quantity or a reduction in dietary carotenoids. Also, only 65% of studies included in our analyses reported an effect of nutrient limitation on body size as well as on ejaculate traits.…”
Section: (4) Publication Bias and Gaps In The Literaturementioning
confidence: 81%
“…Simmons, Tomkins, & Hunt, 1999;Perry & Rowe, 2010;Mehlis et al, 2015), while others have found no effect of diet on such traits (e.g. Sitzmann et al, 2010;Sullivan, Brown, & Clotfelter, 2014). Identifying and accounting for key sources of biological variation in ejaculate investment could help to make sense of such variable results.…”
Section: (2) Special Challenges In Research On Ejaculate Condition Dementioning
confidence: 99%